Housing as a social determinant of health and wellbeing: developing an empirically-informed realist theoretical framework - Steve Rolfe; Lisa Garnham; Jon Godwin; Isobel Anderson; Pete Seaman; Cam Donaldson (BMC, 2020)
Abstract Background The role of housing as a social determinant of health is well-established, but the causal pathways are poorly understood beyond the direct effects of physical housing defects. For low-income, vulnerable households there are particular challenges in creating a sense of home in a new tenancy which may have substantial effects on health and wellbeing. This study examines the role of these less tangible aspects of the housing experience for tenants in the social and private rented sectors in west central Scotland. Methods The paper analyses quantitative data from a mixed methods, longitudinal study of tenants from three housing organisations, collected across the first year of their tenancy. The paper postulates causal hypotheses on the basis of staff interviews and then uses a Realist Research approach to test and refine these into a theoretical framework for the connections between tenants' broader experience of housing and their health and wellbeing. Results Housing service provision, tenants' experience of property quality and aspects of neighbourhood are all demonstrated to be significantly correlated with measures of of health and wellbeing. Analysis of contextual factors provides additional detail within the theoretical framework, offering a basis for further empirical work. Conclusions The findings provide an empirically-informed realist theoretical framework for causal pathways connecting less tangible aspects of the housing experience to health and wellbeing. Applying this within housing policy and practice would facilitate a focus on housing as a public health intervention, with potential for significant impacts on the lives of low-income and vulnerable tenants. The framework also offers a basis for further research to refine our understanding of housing as a social determinant of health.